BERITA PERUBAHAN IKLIM KONSTRUKTIF: MEMOTIVASI GENERASI Z UNTUK AKSI IKLIM - Ariestyani, Kencana; Iqlima (Jurnal Studi Komunikasi dan Media, 2024)
Community engagement is widely recognised as essential in addressing the significant challenges posed by climate change, with scholarly research indicating that media coverage and framing of climate issues are crucial for raising awareness and encouraging community involvement. However, climate change reporting often focuses primarily on negative impacts, which can diminish public support for climate action and contribute to climate anxiety. Framing techniques that emphasise potential solutions can be employed to improve climate change communication. This approach aligns with constructive journalism, emphasising solutions-based reporting, providing credible coverage of social issues like climate change, and fostering democratic dialogue. This study investigates how constructive climate change news can inspire Gen-Z in Indonesia to participate in climate action, as they are projected to be among the most affected by climate change. Using focus group discussions (n=10) with Gen-Z participants, this study employed constructive climate change news as a stimulus before the discussions. Data were analysed through thematic analysis, which revealed two main themes. First, Gen-Z participants felt motivated to engage in climate action after reading constructive climate change news. Second, while Gen-Z expresses a strong willingness to contribute to climate initiatives, two external factors emerged as key facilitators of their involvement in climate action.